Effects of Integration of Social Marketing and Health Belief Model for Preventing Cholangiocarcinoma in High-Risk Areas of Thailand: A Community Intervention Study - Siwaporn Pungpop; Nopparat Songserm; Monthicha Raksilp; Somkiattiyos Woradet; Wanich Suksatan (SAGE Publishing, 2022)
Introduction/Objective: To examine the effects of applying social marketing and Health Belief Model (HBM) in preventing cholangiocarcinoma (CCA) in high-risk areas of Thailand. Methods: About 2 randomized high-risk areas of CCA from multiple-stage sampling were assigned as study areas. The 150 participants were allocated to the experimental group, which received a 12-week health education program that applied social marketing and HBM. The comparison group received the usual services. Data were collected by a questionnaire created by the researchers. We employed descriptive, inferential statistics (paired t -test and independent t -test) for normal distribution, while Analysis of Covariance (ANCOVA) was used for mean scores differing before the experiment. Results: After the experiment, the mean scores of the perceived risk of CCA, perceived severity of CCA, perceived benefits of CCA prevention, perceived barriers to CCA prevention, and correct behaviors of CCA prevention in the experimental group were significantly higher than those before the experiment the .05 level. They were also considerably higher than those of the comparison group at the .05 level. Conclusion: This is the first study to integrate social marketing and HBM for CCA prevention. Therefore, formulating policies or measures to prevent disease through public communication will form a model to avoid CCA and create a channel for distributing useful information to the general public.